Improve PV-diesel operating management system considering sun availability time - Syafii Syafii; Muhardika Muhardika; Heru Dibyo Laksono (Bulletin of Electrical Engineering and Informatics, 2023)
This paper presents a hybrid photovoltaic (PV)-diesel management system performance analysis considering weather conditions. The system is designed to operate based on charging current, battery capacity, and loading current. During charging current is decreased but the battery capacity is high, and the PV system remains supplied for low and medium loading current. When the charging current is lowered and the battery capacity is in the middle, the PV system still supplies for low loading current. However, when the charging current decreases and the battery voltage decreased below 22.3 volts, the supply instantly switches to the diesel generator. The charge current is calculated by subtracting the PV current from the load current. A real-time clock is implemented as a timer to guarantee that there is no repetitive switching throughout the night when charging from the panel is missing. The system works automatically through microcontroller control during the day for 9 hours. The improvement that has been obtained is to overcome the problem of repeated switching processes by limiting the transfer process back to PV when sunlight is not available.